Asynchronous multilevel bit-interleaved polar-coded modulation - Hu, Yaoyue (2023)
Asynchronous bit-interleaved polar-coded modulation (A-BIPCM) provides high performance gain over conventional synchronous polar-coded modulation schemes at the expense of higher storage and decoding complexity. To overcome this drawback, this paper proposes a low-complexity polar-coded modulation, referred to as asynchronous multilevel bit-interleaved polar-coded modulation (A-MLBIPCM). The proposed A-MLBIPCM combines spatial coupling and the multilevel structure on polar-coded modulation. By analyzing the polarization diversity and storage complexity of the system, optimal encoding and modulation patterns are proposed to maintain the polarization diversity and reduce the storage complexity. Simulation results show that A-MLBIPCM provides better block-error-rate (BLER) performance than multilevel polar-coded modulation (MLPCM). Compared with A-BIPCM, the proposed scheme delivers about 23.84%–27.34% savings in storage and up to 33.02% savings in calculation complexity with almost no penalty in BLER (the difference is less than 0.1 dB).